Immunohistochemical evaluation of estrogen and progesterone receptors in peripheral and central giant cell granuloma of the jaws - Razavi SM; Talebi A; Movahedian Attar B; Asgari I (Tehran University of Medical Sciences, 2006)
Background and Aim: Giant cell granuloma is a relatively common benign proliferative lesion of the oral cavity. This lesion has a marked gender predilection with more prevalence in females and tendency to rapid growth and recurrence during pregnancy. The aim of this study was the evaluation of specific receptors of sex hormones in giant cell granuloma. Materials and Methods: In this cross-sectional study, twenty five cases of formalin fixed paraffin embedded giant cell granulomas were retrieved from the oral pathology archive of dental school Isfahan University of Medical Sciences. Also twenty five normal oral mucosa biopsies resected during different surgical procedures were prepared as control group. Cases were immunohistochemically stained for estrogen and progesterone receptors using the biotin-streptavidine method. Data were analyzed by SPSS package. Results: Staining for ER/PR markers were negative for the mononuclear stromal cells and multinucleated giant cells in all cases. The epithelial cells and connective tissue stromal cells of the control group were also negative for these receptors. Conclusion: Based on the results of this study, immunostaining for ER/PR was negative in all cases. These findings suggest that in most cases development and growth of this lesion is not directly related to these hormones. However further studies with more sensitive techniques are recommended.